The hydrocarbon potential of the offshore Talara Basin, Peru - Rossello, Eduardo Antonio (2022)
The offshore Talara Basin is the western extension of the hydrocarbon producing onshore fields since the mid-1800s area of Peru and is also located above the subduction zone of the active continental margin of South America. The offshore portion was evaluated using high quality 3D seismic where mapping horizons are all unconformities within the Eocene as well as the unconformities at the top Paleocene and top Cretaceous. Possible source rocks are the Cretaceous black marine shales of the Campanian Redondo Formation, the limestones of the Albian Muerto Formation, and the marine shales of the Paleogene. The primary target offshore is expected to be deep-water turbidites of Paleocene/Eocene age with a depositional source from the northeast from highlands created by the compressional uplift of the Andes. The main seals offshore are expected to be shales of the upper Eocene Lagunitos Formation and shales in the Chacra Formation, which are also seals in the onshore Litoral field. Thermal maturation modeling shows that two hydrocarbon kitchens exist in the offshore portion of the Talara basin, one in the north and one in the south. The probable Cretaceous source rocks reached the onset of maturity (VR = 0.63%) at a depth of 3,250 to 3,285 m (10,663 ? 10,778 ft) between 30 and 39 Ma (Late Eocene to Oligocene). Importantly, the Cretaceous source rocks stay within the oil window once they enter it in the late Eocene. Satellite studies show a large offshore present-day oil seep in the southern part of the basin and 3D seismic shows direct hydrocarbon indicators (DHIs) imaged as flat spots and bottom simulating reflectors (BSR). Basin modeling suggests hydrocarbon migration pathways would have been updip (to the east) into the onshore traps and would therefore have first filled the offshore traps along the migration pathway. We conclude that the Talara Basin offshore offers excellent exploration opportunities in a proven productive area where multiple prospects have been mapped.